2020
DOI: 10.3389/fmed.2020.00306
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hemoglobin Disorders During the COVID-19 Pandemic

Abstract: The coronavirus disease 2019 (COVID-19) is an emerging infectious disease that has become a global public health concern after being first reported in China and has subsequently spread worldwide. It causes mild to severe respiratory illness with some flu-like symptoms. The causal virus behind this disease, SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), conceivably attacks the receptors of the respiratory system of the human body but has no strict evidence of attacking the blood cells yet. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 48 publications
0
39
0
2
Order By: Relevance
“…In addition, we confirmed that people with weakened immune systems from a medical condition or treatment are at a higher risk. Among these, those living with haemoglobin disorders [ 49 ], inflammatory bowel disease [ 50 ] and immune-rheumatological diseases [ 51 ] must be considered vulnerable groups for SARS-CoV-2 infection. Mental health and cognitive function might have independent utility in understanding the burden of respiratory disease, since they may influence the risk of contracting the infection, at least in part by impairing innate or adaptive immunity [ 52 ] and diminishing the precautions taken to minimize risk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we confirmed that people with weakened immune systems from a medical condition or treatment are at a higher risk. Among these, those living with haemoglobin disorders [ 49 ], inflammatory bowel disease [ 50 ] and immune-rheumatological diseases [ 51 ] must be considered vulnerable groups for SARS-CoV-2 infection. Mental health and cognitive function might have independent utility in understanding the burden of respiratory disease, since they may influence the risk of contracting the infection, at least in part by impairing innate or adaptive immunity [ 52 ] and diminishing the precautions taken to minimize risk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we confirmed that people with weakened immune systems from a medical condition or treatment are at a higher risk. Among these, those living with haemoglobin disorders [42], inflammatory bowel disease [43] and immune-rheumatological diseases [44] must be considered vulnerable groups for Covid-19…”
Section: Discussionmentioning
confidence: 99%
“…Even with the limited clinical evidence, it is noticeable that patients with pre-existing blood disorders are amongst those most vulnerable to SARS-CoV-2 infection, and that those at risk of developing blood abnormalities may have a poorer prognosis of the COVID-19 disease. Hence, initial detection and close monitoring of haemoglobin levels in infected patients should be contemplated ( Chowdhury and Anwar, 2020 ).…”
Section: The Association Between Covid-19 and The Most Common Chronicmentioning
confidence: 99%
“…With the continuing spread of COVID-19, individuals with haemoglobin disorders remain of the most vulnerable populations. To date, inadequate research is available to verify the link between these disorders and COVID-19; however, the haematology community continues to effectively minimize the risk of patients facing new emerging threats ( Chowdhury and Anwar, 2020 ). Sickle cell patients, for example, are often treated with hydroxycarbamide (hydroxyurea), a cytotoxic agent, having possible immune-compromising effects.…”
Section: The Association Between Covid-19 and The Most Common Chronicmentioning
confidence: 99%